Mexican mosquitoes: overcoming barriers for dengue and Zika virus infection - Garcia Luna, Selene M., author; Black, William C., IV, advisor; Ebel, Gregory D., committee member; Perera, Rushika, committee member; Hess, Ann M., committee member (Colorado State University. Libraries, 2017)
The mosquito transmitted arboviruses cause an important burden of disease worldwide. In Latin America dengue disease is endemic with more than 1 million dengue fever cases reported yearly. In addition to dengue, chikungunya and Zika viruses have been also circulating since their introduction in 2014 and 2015 respectively. For a mosquito-borne infection to occur susceptible humans, the mosquito vector and the virus should coincide. This dissertation was focused in the mosquito vector and its ability to acquire, maintain and then transmit the virus, termed vector competence. The vector competence was a fundamental measure for the research chapters in which we studied different aspects on the interactions between Aedes aegypti and Aedes albopictus mosquitoes and Dengue-2 and Zika viruses. This dissertation includes three research chapters which were based on the following specific aims. Specific aim 1: Determine the patterns of gene flow and vector competence for DENV-2 of Aedes aegypti from around the Mexican Neovolcanic Axis. It was previously reported that the intersection of the Neovolcanic axis (NVA) with the Gulf of Mexico coast in the state of Veracruz acts as a discrete barrier to gene flow among Ae. aegypti populations north and south of the NVA. These collections also differed in their vector competence (VC) for Dengue virus serotype 2 (DENV-2). Therefore, the goal of the present study was to determine if the same patterns remained 8 years later in collections from 2012. For which haplotype variation for the mitochondrial ND4 and the nuclear genes Dicer-2 and Argonaute-2 was analyzed for north and south of the NVA mosquito populations. Also, the VC of those populations for DENV-2 was determined (Chapter 2). Specific aim 2: Profile the microRNA response of Aedes aegypti midguts to DENV-2 exposure and DENV-2 infection. The microRNA pathway has been found to modulate important physiological mechanisms in mosquito vectors. Therefore in the context of DENV infection, miRNA modulation may provide information about key genes that are important for infection. Differential expression patterns of miRNAs from mosquito midguts upon infection have been unexplored. Therefore, we explored on the involvement of the miRNA pathway in persistently DENV-2 infected mosquitoes, for which DENV-2 virus was detected at 14 days post-infection (dpi). Two comparisons were included in the study. In the first group, DENV-2 infected midguts that produced a disseminated infection (did not have a midgut escape barrier) were contrasted with those that were given a non-infectious blood meal. Also, we included a comparison group from a subset of mosquitoes from the same cohort that were exposed to DENV-2 regardless of their midgut infection status contrasted to unexposed mosquitoes. Analysis of miRNA regulation in mosquitoes may help us to understand more about the intricate interactions between the virus and the vector host (Chapter 3). Specific aim 3: Assess the variation in competence for Zika virus transmission by Aedes aegypti and Aedes albopictus from Mexico. Previous studies have reported low Zika virus (ZIKV) transmission rates for the Asian lineage of ZIKV using mosquitoes from a wide geographical range from the Americas. Beside low transmission rates we hypothesized that VC is variable and is highly dependent upon the geographic origin of the mosquito populations. Hence, we analyzed the ZIKV transmission potential of recently colonized Aedes collections. Ten Ae. aegypti and three Ae. albopictus collections from different locations across Mexico were analyzed for ZIKV (strain PRVABC59 Asian genotype) vector competence at 7 and 14 dpi. We calculated the additive contribution of each of the four transmission barriers to ZIKV infection. In addition, we evaluated the contribution of both mosquito species to ZIKV transmission in areas where their distributions overlap (Chapter 4).
Keywords: Dengue virus; vector competence; Mexico; Aedes; Zika virus